Pelatihan Penulisan Kreatif Sastra Berbasis Kekayaan Lahan Gambut di Kalimantan Tengah Bagi Siswa SMP Kota Palangka Raya Tahun 2024 - Syarah Veniaty; Patrisia Cuesdeyeni; Silvia Norma Leli; Sahiratun Nissa; Amalia Kartika sari; Justatia Hakiki; Misnawati Misnawati (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
Central Kalimantan as part of the province that has the second largest peatland in Indonesia is currently facing the threat of extinction of the land. Therefore, peat ecosystem conservation needs to be continuously carried out by all levels of society, including the next generation who are currently still studying at elementary, middle and high school levels. Participation in peatland conservation activities can be started in a simple way and closely related to the lives of children and adolescents, one of which is through writing literary works such as short stories. Literary works can be an educational medium that is full of messages for its readers. The objectives of this community service activity; (1) to improve the ability of junior high school students in Palangka Raya City in writing creative literature, especially short stories based on the wealth of peatlands in Palangka Raya, (2) to improve the knowledge and insight of junior high school students in Palangka Raya City regarding the wealth of peatlands in Palangka Raya City, and (3) to maintain literature based on the wealth of peatlands in Central Kalimantan. The method used in this community service activity is a process method that includes three stages, namely; (1) preparation, (2) implementation and (3) evaluation. The result of this activity is a product, namely the Anthology of Short Stories Uncovering the Mystery and Wonders of Central Kalimantan Peatlands, which is the work of the participants of this training activity. This product also shows that this writing training activity is able to improve the ability of junior high school students in Palangka Raya City in writing creative literature.